Rachel Augustine Potter, Bending the Rules: Procedural Politicking in the Bureaucracy, Chicago, University of Chicago Press, 2019, 256 pp. - Guzmán González, Patricia (Gestión y Política Pública, 2020)
Reseña de Patricia Guzmán González para el libro “Bending the Rules: Procedural Politicking in the Bureaucracy” de Rachel Augustine Potter.